Vaccination With the Commensal Streptococcus mitis Expressing Pneumococcal Serotype 5 Capsule Elicits IgG/IgA and Th17 Responses Against Streptococcus pneumoniae - Shekhar, Sudhanshu; Åmdal, Heidi A.; Petersen, Fernanda Cristina (Frontiers in Immunology, 2021)
Recent studies have identified a clinical isolate of the commensal Streptococcus mitis that expresses Streptococcus pneumoniae serotype 5 capsule (S. mitis serotype 5) and shows serospecificity toward pneumococcal serotype 5. However, it remains unknown whether S. mitis serotype 5 induces protective immunity against pneumococcal serotype 5. In this study, we evaluated the ability of S. mitis serotype 5 to generate protective immunity in a mouse model of lung infection with pneumococcal serotype 5. Upon challenge infection with S. pneumoniae serotype 5, mice intranasally immunized with S. mitis serotype 5 exhibited reduced pneumococcal loads in the lungs, nasal wash, and bronchoalveolar lavage fluid compared with those receiving PBS (control). The immunized mice displayed significantly higher levels of IgG and IgA antibodies reactive to S. mitis serotype 5, S. pneumoniae serotype 5 or S. pneumoniae serotype 4 than the antibody levels in control mice. In vaccinated mice, the IgG/IgA antibody levels reactive to S. mitis serotype 5 or S. pneumoniae serotype 5 were higher than the levels reactive to S. pneumoniae serotype 4. Furthermore, in-vitro restimulation of the lung-draining mediastinal lymph node cells and splenocytes from immunized mice with killed S. mitis serotype 5, S. pneumoniae serotype 5 or S. pneumoniae serotype 4 showed enhancedTh17, but not Th1 and Th2, responses. Overall, our findings show that mucosal immunization with S. mitis serotype 5 induces Th17 and predominant serotype-specific IgG/IgA antibody responses against pneumococcal infection.